2013
DOI: 10.1080/10810730.2013.768732
|View full text |Cite
|
Sign up to set email alerts
|

Food Marketing to Children on U.S. Spanish-Language Television

Abstract: Latino children in particular are at risk of childhood obesity. Because exposure to televised food marketing is a contributor to childhood obesity, it is important to examine the nutritional quality of foods advertised on Spanish-language children's programming. The authors analyzed a sample of 158 Spanish-language children's television programs for its advertising content and compared them with an equivalent sample of English-language advertising. The authors evaluated nutritional quality of each advertised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…However, there have been no studies on racial/ethnic-or income-specific food wastage to date (25,26). Meanwhile, studies on food marketing toward children suggest that the food industry may be marketing certain NB products more heavily toward NHB and lower-income areas (27)(28)(29)(30) or marketing nutritionally poor food products toward Spanishspeaking children (31), affecting their food culture (32). This might encourage brand loyalty and could explain the slower decline among NHB, Hispanic, and lowest-income households over time for HWCF and other NB foods.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no studies on racial/ethnic-or income-specific food wastage to date (25,26). Meanwhile, studies on food marketing toward children suggest that the food industry may be marketing certain NB products more heavily toward NHB and lower-income areas (27)(28)(29)(30) or marketing nutritionally poor food products toward Spanishspeaking children (31), affecting their food culture (32). This might encourage brand loyalty and could explain the slower decline among NHB, Hispanic, and lowest-income households over time for HWCF and other NB foods.…”
Section: Discussionmentioning
confidence: 99%
“…Across the studies included in this review, television viewing was associated with a higher weight status for children who viewed more than 2 hours of television per day compared to those who did not. 19,20 Studies also showed higher rates of TVs in bedrooms of Latino (74%) children compared with white children (22%). 18 …”
Section: Overview Of Findingsmentioning
confidence: 96%
“…Most schools (92%) issue digital devices such as laptops and tablets to students and require them to access the Internet on these devices at school and for homework. This was especially true for districts serving primarily minority students, underscoring existing evidence which demonstrates that students in those districts are at greater risk of exposure to food marketing …”
Section: Discussionmentioning
confidence: 56%
“…Children are exposed to unhealthy food advertising in many settings and by a variety of channels, including electronic media . In addition, compared with white children, African‐American and Latino children—who are at higher risk of obesity and diet‐related chronic disease—are exposed to higher levels of marketing for unhealthy food and beverages …”
mentioning
confidence: 99%